Study of the renal profile in relation to CD4 count in human immuno-deficiency virus patients from a tertiary centre of Bihar - Prakash, Jyoti; Das, Bhagwan; Beernandi, Chiranjeevi; Kumar, Munish (International Journal of Research in Medical Sciences, 2022)
Background: Human immuno-deficiency virus (HIV)-positive individuals are at increased risk for kidney disease, including HIV-associated nephropathy (HIVAN). HIV peptides rather than infection may be more important in pathogenesis of HIVAN. Much has been learnt about the pathogenesis and treatment of HIV-associated renal diseases because of the development of animal models and the molecular evaluation of clinical samples. Methods: We studied 90 consecutive patients with HIV and allocated them into 3 groups, each containing 30 patients on the basis of their CD4 counts. Then each group was divided into two subgroups, X and Y on the basis of whether they received anti-retroviral treatment (HAART) or not. Subgroup X received HAART and subgroup Y did not received HAART. Results: There was male preponderance (M: F=5.4: 1). Microalbuminuria, increased serum creatinine and decreased GFR was highest among HIV patients having CD4 count below 200 as compared to those having CD4 count of 200-350 and above 350. Conclusions: Our study demonstrates that both proteinuria and HIVAN are common in HIV infected patients. Proteinuria and glomerular filtration rate have a negative correlation with the CD4 count.